Additivity dominance: Additivites are more potent and more often lexicalized across languages than are “subtractives” - Paul Rozin; Claude Fischler; Christy Shields-Argelès (Judgment and Decision Making, 2009)
Judgments of naturalness of foods tend to be more influenced by the process history of a food, rather than its actual constituents. Two types of processing of a “natural” food are to add something or to remove something. We report in this study, based on a large random sample of individuals from six countries (France, Germany, Italy, Switzerland, UK and USA) that additives are considered defining features of what makes a food not natural, whereas “subtractives” are almost never mentioned. In support of this, skim milk (with major subtraction of fat) is rated as more natural than whole milk with a small amount of natural vitamin D added. It is also noted that “additives” is a common word, with a synonym reported by a native speaker in 17 of 18 languages, whereas “subtractive” is lexicalized in only 1 of the 18 languages. We consider reasons for additivity dominance, relating it to omission bias, feature positive bias, and notions of purity.